Advanced ultrawide-field optical coherence tomography angiography identifies previously undetectable changes in biomechanics-related parameters in nonpathological myopic fundus - Zhang, Weiran; Li, Chang; Gong, Yibo; Liu, Nianen; Cao, Yunshan; Li, Zhiqing; Zhang, Yan (Frontiers in Bioengineering and Biotechnology, 2022)
Purpose: To detect the previously undetectable changes in vessel density and structural thickness, the 2 biomechanic-related parameters reflecting hemodynamics and tensile strength, respectively, in peripheral and central fundi of nonpathological myopic eyes with an advanced ultrawide-field OCTA system. Methods: A cross-sectional observational clinical study was carried out by recruiting 155 eyes from 79 college students aged 18 to 28 years. The eyes were stratified into normal, low myopia, medium myopia, and high myopia groups according to diopter. A newly-developed OCTA system with scanning dimensions of 24 mm × 20 mm, acquisition speed of 400 KHz, and imaging range of 6 mm was used to examine the vessel densities of superficial vascular complex (SVC), deep vascular complex (DVC), choriocapillary (ChC), and choroidal vessel (ChV) layers as well as the thicknesses of inner retina, outer retina, and choroid in the nonpathological myopic eyes. Results: The vessel densities in ChV at temporal, inferotemporal, inferior, and inferonasal regions in fundus periphery were significantly reduced in myopic subjects as compared to normal controls (all p < 0.05). The thicknesses of inner retina segments in most peripheral regions of the fundus became attenuated along with myopia severity (all p < 0.05). The thicknesses of outer retina segments were diminished at superior and supranasal regions of peripheral fundi of myopic subjects as compared to normal controls (all p < 0.05). At central macular region, the decreased vessel densities of SVC and DVC were correlated with the attenuated thicknesses of inner retina segments, respectively (all p < 0.05). Conclusion: As revealed for the first time by the advanced ultrawide-field OCTA system, the 2 biomechanic-related parameters including the densities of choroidal vessels and thicknesses of inner retina segments were significantly reduced in the periphery of nonpathological myopic fundi and the reductions were associated with myopia severity. At the central macular region, the newly-developed device provides consistent results with the previous findings. Therefore, it is important to use the non-invasive, ultrawide-field OCTA with high resolution for early detection of fundus changes in subjects with nonpathological high myopia.